Case Report: Robust and durable response to the combination of tislelizumab and chemotherapy in advanced thymic epithelial tumors: a case series - Zhang, Lantian; Zhang, Yuqi; Li, Shuke; Wang, Yan; Yu, Yue; He, Jing; Gao, Wen (Frontiers in Immunology, 2025)
BackgroundThymic epithelial tumors (TETs), categorized predominantly as thymoma (T) or thymic carcinoma (TC), face a challenging prognosis and limited treatment options. Although chemotherapy remains the established treatment for advanced TETs, its responses tend to be short-lived. The emergence of immunotherapy, particularly programmed cell death-1 (PD-1) and programmed death ligand-1 inhibitors (PD-L1), is increasingly being regarded as a promising new treatment option for various malignancies.MethodsHerein, we present a case series of eight patients with TETs who received tislelizumab treatment at Jiangsu Provincial Hospital between 2021 and 2023. All cases were histologically confirmed as either thymoma or thymic carcinoma. Among these eight cases, six patients (5 thymic carcinomas [TC] and 1 thymoma [T]) received tislelizumab in combination with chemotherapy following multiple cycles of prior chemotherapy without achieving significant therapeutic response. Two TC patients were administered this combination regimen as first-line treatment. Following the initiation of immunotherapy, patients received tislelizumab at a dose of 200 mg every three weeks until disease progression or the occurrence of unacceptable toxicity. Treatment response was assessed by the investigators according to the Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1 guidelines.ResultsThe 8 patients described had a median age of 59 years (range, 47-72). During the course of immunotherapy, five patients (62.5%) achieved partial response, and notably, even after transitioning to maintenance therapy with tislelizumab, the lesions continued to shrink, with the longest sustained partial response lasting over 2 years. Three patient (37.5%) experienced stable disease as their best response to immunotherapy. Among all these patients, three patients (37.5%) demonstrated initial efficacy but subsequently exhibited progressive disease (median progression-free survival of 14 months). All patients are still being followed up, with the longest PFS extending to 31 months. Notably, five of the eight patients underwent PD-L1 testing and were all found to be negative. Despite this, no immune-related Grade 3–5 adverse events (AEs) were reported and all AEs were manageable with supportive measures. Grade 1–2 AEs were adrenal insufficiency (n=1), thyroid dysfunction (n=1), and pneumonia (n=1).ConclusionsOur study findings suggest that the combination of immunotherapy and chemotherapy yields durable clinical responses in patients with TETs, suggesting its potential as a safe and effective first-line treatment strategy for advanced TETs. Notably, the therapeutic benefits of chemo-immunotherapy appear to extend beyond patients with high PD-L1 expression (≥50%), indicating that this treatment approach may not be strictly limited to individuals with elevated PD-L1 levels.